2020
DOI: 10.15171/ijoem.2020.1572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Densities of 50 Hz Electromagnetic Field on Serum IL-9, IL-10, and TNF-α Levels

Abstract: Background: Extremely low-frequency electromagnetic fields (ELF-EMFs) are abundantly produced in modern societies. In recent years, interest in the possible effects of ELF-EMFs on the immune system has progressively increased. Objective: To examine the effects of ELF-EMFs with magnetic flux densities of 1, 100, 500, and 2000 µT on the serum levels of interleukin (IL)-9, IL-10, and tumor necrosis factor-alpha (TNF-α). Methods: 80 adult male rats were exposed to ELF-EMFs at a frequency of 50 Hz for 2 h/day for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In fact, 50 Hz of exposure induced an early increase of IL-1β, IL-18, and TNFα production and secretion by keratinocytes and fibroblasts, while a later inhibition of inflammatory mediators led to healing, mirroring the physiological process of wound repair [ 52 , 53 , 54 ]. In accordance, in vivo and in vitro studies reported the influence of ELF-EMFs exposure on inflammatory state promotion, with increased production of pro-inflammatory cytokines, such as IL-6, IL-9, and TNF-α, and increased levels of ROS [ 55 , 56 ]. Furthermore, ex vivo studies reported the ability of ELF-EMFs exposure in activating the anti-inflammatory response by down-modulating pro-inflammatory cytokines, inducing IL-10, and transforming growth factor β (TGFβ), as a key antagonist of pro-inflammatory mediators [ 55 , 57 ], which enhanced the immune system response in the damaged areas and favored early wound healing.…”
Section: Emf-elf and Wound-repair: Mechanism Of Actionmentioning
confidence: 71%
See 1 more Smart Citation
“…In fact, 50 Hz of exposure induced an early increase of IL-1β, IL-18, and TNFα production and secretion by keratinocytes and fibroblasts, while a later inhibition of inflammatory mediators led to healing, mirroring the physiological process of wound repair [ 52 , 53 , 54 ]. In accordance, in vivo and in vitro studies reported the influence of ELF-EMFs exposure on inflammatory state promotion, with increased production of pro-inflammatory cytokines, such as IL-6, IL-9, and TNF-α, and increased levels of ROS [ 55 , 56 ]. Furthermore, ex vivo studies reported the ability of ELF-EMFs exposure in activating the anti-inflammatory response by down-modulating pro-inflammatory cytokines, inducing IL-10, and transforming growth factor β (TGFβ), as a key antagonist of pro-inflammatory mediators [ 55 , 57 ], which enhanced the immune system response in the damaged areas and favored early wound healing.…”
Section: Emf-elf and Wound-repair: Mechanism Of Actionmentioning
confidence: 71%
“…In accordance, in vivo and in vitro studies reported the influence of ELF-EMFs exposure on inflammatory state promotion, with increased production of pro-inflammatory cytokines, such as IL-6, IL-9, and TNF-α, and increased levels of ROS [ 55 , 56 ]. Furthermore, ex vivo studies reported the ability of ELF-EMFs exposure in activating the anti-inflammatory response by down-modulating pro-inflammatory cytokines, inducing IL-10, and transforming growth factor β (TGFβ), as a key antagonist of pro-inflammatory mediators [ 55 , 57 ], which enhanced the immune system response in the damaged areas and favored early wound healing. A clinical and experimental investigation showed that ELF-EMF speed up the switch from an inflammatory phase to a proliferative phase in the wound healing.…”
Section: Emf-elf and Wound-repair: Mechanism Of Actionmentioning
confidence: 71%
“…In fact, physicists have long maintained that such a low field strength EMF cannot achieve biological effects because the energy deposited is negligible. From in vitro studies, it is known that even minor exposure to LF‐EMF can have effects on cellular mechanisms [Mahaki et al, 2019]. Indeed, it was found that cells are responsive to field strengths as low as ~0.15 µT [Kapri‐Pardes et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…The latest reports showed that 1 and 100 μT 50 Hz ELF-MF not only downregulates proinflammatory cytokines (IL-9 and TNF-α), but also activates an inflammation-suppressing cytokine, IL-10. In this case, the most noticeable effect was obtained at the highest value of magnetic induction [ 131 ]. The ELF-MF (60 Hz, 10 mT) also mitigated the deficits in ischemic mice, among others in the context of immune function: the levels of inflammatory mediators MMP9 and IL-1β were decreased [ 102 ].…”
Section: Elf-mf-induced Changes In Levels Of Neurotransmitters Homentioning
confidence: 99%